2015
DOI: 10.1111/hiv.12315
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor (suPAR) is a novel, independent predictive marker of myocardial infarction in HIV‐1‐infected patients: a nested case‐control study

Abstract: ObjectivesPatients infected with HIV are at increased risk of myocardial infarction (MI). Increased plasma levels of the inflammatory biomarker soluble urokinase plasminogen activator receptor (suPAR) have been associated with increased risk of cardiovascular diseases (CVD), including MI in the general population. We tested suPAR as a predictive biomarker of MI in HIV‐1‐infected individuals.MethodssuPAR levels were investigated in a nested case‐control study of 55 HIV‐1‐infected cases with verified first‐time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Furthermore, in patients with known atherosclerosis, elevated suPAR may additionally represent significant endothelial dysfunction associated with CAD, thus providing a more specific marker that incorporates several disease pathways, as opposed to hsCRP [9]. While elevations in suPAR have been associated with adverse outcomes in a wide variety of disease processes [11,13,[32][33][34], it has more recently shown promise as a predictor of incident cardiovascular events [10,15,35]. Both serum and intraplaque levels of suPAR were elevated in patients with symptomatic carotid atherosclerosis, suggesting its potential utility in identifying a vulnerable plaque phenotype [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in patients with known atherosclerosis, elevated suPAR may additionally represent significant endothelial dysfunction associated with CAD, thus providing a more specific marker that incorporates several disease pathways, as opposed to hsCRP [9]. While elevations in suPAR have been associated with adverse outcomes in a wide variety of disease processes [11,13,[32][33][34], it has more recently shown promise as a predictor of incident cardiovascular events [10,15,35]. Both serum and intraplaque levels of suPAR were elevated in patients with symptomatic carotid atherosclerosis, suggesting its potential utility in identifying a vulnerable plaque phenotype [36].…”
Section: Discussionmentioning
confidence: 99%
“…suPAR has been widely studied in a variety of infectious diseases, including sepsis [ 23 ], tuberculosis [ 24 ], and HIV infection [ 25 ]. Savva et al demonstrated that suPAR is a reliable predictor of severity of sepsis and can independently predict unfavourable outcomes in both ventilator-associated pneumonia and sepsis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated soluble urokinase-type plasminogen activator receptor (suPAR) is an inflammation marker and has recently been identified as a predictor of MI in HIVinfected patients [93].…”
Section: The Role Of Hiv Infection In Itself In the Pathogenesis Of Cmentioning
confidence: 99%